Sosialisasi dan Pendampingan dalam Pengembangan Kapasitas Usaha Mikro Kecil Menengah (UMKM) di Desa Kaliputu Kecamatan Kota Kabupaten Kudus - Amrullah, Ulya Fajar; Rizka Dami Ristanto; Nadila Silviatun; Nala Izza Sofiana (Universitas Negeri Semarang, 2025)
SMEs (Micro, Small, and Medium Enterprises) play a crucial role in Indonesia's economy but often face challenges such as a lack of entrepreneurial mindset and managerial skills. This study aims to address the challenges faced by SMEs in Kaliputu Village, particularly jenang (traditional sweet) entrepreneurs, by strengthening their entrepreneurial mindset and providing training in business management, marketing strategies, and financial management. The methods used include socialization, regular training, and practical assistance. The subjects of this community service are the jenang SMEs in Kaliputu Village. The results show a significant increase in market reach and sales of jenang products, as well as improvements in business quality. Promotional videos and Shopee accounts have successfully expanded product visibility, while training has enhanced managerial, marketing, and financial management skills. This initiative not only helps to improve the knowledge and skills of jenang entrepreneurs but also boosts their confidence in facing increasingly tough market competition. With this program, SMEs in Kaliputu Village become more prepared and competitive in facing future business challenges. This community service has provided longterm positive impacts for the development of SMEs in Kaliputu Village, making them more competitive in a broader market and sustainable in running their businesses.